Non-adherence to labor guidelines in cesarean sections done for failed induction and arrest of dilation...Society of Maternal Fetal Medicine 2018, Poster presentation, Abstract #832, Dallas, TX, January 29th-February 3rd, 2018. - Escobar, Christina M.; Grünebaum, Amos; Nam, Eunice Y.; Olson, Amber T.; Anzai, Yuzuru; Benedetto-Anzai, Maria Teresa; Cheon, Teresa; Arslan, Alan; McClelland, W. Spencer (Journal of Perinatal Medicine, 2021)
In 2014, the American College of Obstetrics and Gynecology published guidelines for diagnosing failed induction of labor (FIOL) and arrest of dilation (AOD) to prevent cesarean delivery (CD). The objectives of this study were to determine the rate of adherence to these guidelines and to compare the association of guideline adherence with physician CD rates and obstetric/neonatal outcomes. Retrospective cohort review of singleton primary cesarean deliveries for FIOL and AOD at a single academic institution from 2014 to 2016. Univariate and multivariate analyses were used to compare adherence to the guidelines with physician CD rates and obstetric/neonatal outcomes. Of the 591 cesarean deliveries in the study, 263 were for failed induction, 328 for AOD and 79% (468/591) were not adherent to the American College of Obstetricians and Gynecologists and the Society for Maternal-Fetal Medicine (ACOG/SMFM) guidelines. Of the failed inductions, 82% (215/263) and of the AODs 77% (253/328) were not adherent. There was no difference between adherent and non-adherent CDs with regard to maternal characteristics, or obstetric/neonatal outcomes. Duration of oxytocin use after rupture of membranes, dilation at time of CD, and birth weight were statistically higher in adherent CDs. On multivariate linear regression, physician CD rates were inversely correlated with adherence to ACOG/SMFM guidelines (p<0.0001), gestational age (p=0.007), and parity (p=0.003). Our study shows that physician non-compliance with ACOG guidelines was high. Adherence to these guidelines was associated with lower physician CD rates, without an increase in obstetric or neonatal complications.